Crossing language boundaries. The use of English in advertisements in Polish lifestyle magazines - Dąbrowska, Marta (LingBaW. Linguistics Beyond and Within, 2022)
Advertising is an area open to various types of innovation and a creative use of language. Advertisers use a variety of strategies to attract as many customers as possible, employing enticing visuals, clever puns, detailed descriptions, direct appeals, etc. Yet, if the product is to sell, it appears self-evident that the language of the advertisement should not constitute a barrier. Contrary to this assumption, however, there has been an ever growing trend visible in Polish magazines for the last two decades to formulate parts of or even complete advertisements, not infrequently of Polish brands, in English, despite the fact that English remains a foreign language in Poland, although, admittedly, a very popular one. The present study is conducted within the framework of sociolinguistically informed linguistic landscape analysis. It investigates the visibility of English in the advertising landscape of lifestyle magazines published in Poland, represented by a selection of high quality and mid-range general interest and specialised women’s and men’s magazines. Its objective is to identify tendencies in the manifestations of this newly developing multilingualism in respect of the frequency of using English, the category of advertised products which particularly often appear in such multilingual advertisements as well as the type of magazines which admit such advertisements rather readily. Regarding the linguistic strategies used in the analysed texts, attempts are made to establish whether English tends to be used in complete texts and sentences or only parts of those, and if the latter, which elements of the genre of advertising are especially marked by such language choices and why.